TINGKAT KEPEMIMPINAN MAHASISWA SETELAH MENGGUNAKAN SPORT EDUCATION BULU TANGKIS - Agustin, Nur Mahfuzah; Oktora Mudzakir, Dicky; Naim Fadilah, Dedi (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aimed to determine the level of student leadership in appropriate roles in Sport Education after using Sport Education Badminton. Materials and Methods. The research method used a quantitative descriptive approach. The participants in the study were 22 students of one of the sports study programs in the Indramayu district. The research instrument used the ILI-SF. Data analysis techniques using descriptive statistics. Results. The results concluded that student leadership according to roles in Sports Education after using Badminton Sports Education tended to be in the Good category. Conclusions. This study concludes that further research is needed by using a pre-test before using Sports Education on leadership so that the results obtained can be generalized according to the previously updated research instrument and the relationship between the results of leadership and motivation.